2022
DOI: 10.6007/ijarbss/v12-i10/15117
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure in Small and Medium Enterprises in Malaysia: An Exploratory Factor Analysis

Abstract: It is theoretically acknowledged that decisions on capital structure remain an important goal to maximise returns. This study seeks to identify factors influencing the capital structure of Malaysia's small and medium enterprises (SMEs) through re-assessment of the operationalisation of constructs and an evaluation of certain assumptions on capital structure choices. An analysis of 500 questionnaires from SMEs located in the central region of Peninsular Malaysia was considered in the context of reliability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Credit history refers to the relationship between the micro-entrepreneur and the lender bank and non-bank lenders (Nawi, 2015). It is usually measured as the number of loans and services taken by the borrower and successfully repaid.…”
Section: Methodsmentioning
confidence: 99%
“…Credit history refers to the relationship between the micro-entrepreneur and the lender bank and non-bank lenders (Nawi, 2015). It is usually measured as the number of loans and services taken by the borrower and successfully repaid.…”
Section: Methodsmentioning
confidence: 99%
“…Ramachandran and Yahmadi (2019) reported that lack of basic business knowledge, lack of market knowledge and information, lack of adequate finance, complicated procedures and delay in loan disbursement, limited network, experience, and expertise, reluctant to use modern technology limited SMEs access to finance. A research Nawi (2015) observed that most SMEs in Asia faced major challenges in accessing cheap finance where available ones offered by financial institutions have strenuous lending policies related to collateral and lack of information. Yoshino and Taghizadeh-Hesary (2018) said that SMEs in this region of the world face difficulty in accessing credit because of asymmetric information problems between suppliers and demanders of funds and the high transaction costs.…”
Section: Bank Loan Financing Policies and Smes Performancementioning
confidence: 99%
“…Our sample consisted mainly of respondents registered with Cradle Fund, MaGIC and TeAM which had a balanced ethnic distribution in their databases (Juri, 1999;Nawi, 2015;Noor & Leong, 2013). It is worth mentioning that some TSs were listed with Cradle, MaGIC and TeAM, which reduced the study ' s reach and overall sample.…”
Section: Questionnaire Surveymentioning
confidence: 99%